Proteasome Inhibition Increases Recruitment of IκB Kinase β (IKKβ), S536P-p65, and Transcription Factor EGR1 to Interleukin-8 (IL-8) Promoter, Resulting in Increased IL-8 Production in Ovarian Cancer Cells - Singha, Bipradeb (American Society for Biochemistry and Molecular Biology, 2014)
Proinflammatory and pro-angiogenic chemokine interleukin-8 (IL-8, CXCL8) contributes to ovarian cancer progression through its induction of tumor cell proliferation, survival, angiogenesis, and metastasis. Proteasome inhibition by bortezomib, which has been used as a frontline therapy in multiple myeloma, has shown only limited effectiveness in ovarian cancer and other solid tumors. However, the responsible mechanisms remain elusive. Here, we show that proteasome inhibition dramatically increases the IL-8 expression and release in ovarian cancer cells. The responsible mechanism involves an increased nuclear accumulation of IκB kinase β (IKKβ) and an increased recruitment of the nuclear IKKβ, p65-phosphorylated at Ser-536, and the transcription factor early growth response-1 (EGR-1) to the endogenous IL-8 promoter. Coimmunoprecipitation studies identified the nuclear EGR-1 associated with IKKβ and with p65, with preferential binding to S536P-p65. Both IKKβ activity and EGR-1 expression are required for the increased IL-8 expression induced by proteasome inhibition in ovarian cancer cells. Interestingly, in multiple myeloma cells the IL-8 release is not increased by bortezomib. Together, these data indicate that the increased IL-8 release may represent one of the underlying mechanisms responsible for the decreased effectiveness of proteasome inhibition in ovarian cancer treatment and identify IKKβ and EGR-1 as potential new targets in ovarian cancer combination therapies.